Rangeland production and annual rainfall relations in the Mediterranean Basin and in the African Sahelo-Sudanian zone - Houerou, H.N. le; Hoste, Christian H. (1977)
Correlations between average pasture production and average annual rainfall in the Mediterranean Basin and the African Sahelo - Sudanian Zone.